Differences in Upgrading of Prostate Cancer in Prostatectomies between Community and Academic Practices - Franklin Lee; Henry Gottsch; William J. Ellis; Lawrence D. True; Daniel W. Lin; Jonathan L. Wright (Advances in Urology)
Objective. To determine whether initial biopsy performed by community or academic urologists affected rates of Gleason upgrading at a tertiary referral center. Gleason upgrading from biopsy to radical prostatectomy (RP) is an important event as treatment decisions are made based on the biopsy score. Materials and Methods. We identified men undergoing RP for Gleason 3+3 or 3+4 disease at a tertiary care academic center. Biopsy performed in the community was centrally reviewed at the academic center. Multivariate logistic regression was used to determine factors associated with Gleason upgrading. Results. We reviewed 1,348 men. There was no difference in upgrading whether the biopsy was performed at academic or community sites (OR 0.9, 95% CI 0.7–1.2). Increased risk of upgrading was seen in those with >1 positive core, older men, and those with higher PSAs. Secondary pattern 4 and larger prostate size were associated with a reduction in risk of upgrading. Compared to the smallest quartile of prostate size (<35 g), those in the highest quartile (>56 g) had a 49% reduction in risk of upgrading (OR 0.51, 95% CI 0.3–0.7). Conclusion. There was no difference in upgrading between where the biopsy was performed and community and academic urologists.